2018
DOI: 10.1002/aqc.2949
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and habitat preferences of Hippocampus species along the Apulian coast

Abstract: The aim of this study was to provide further knowledge of the ecological, spatial, and temporal distribution and life‐cycle traits of the sympatric seahorse species Hippocampus hippocampus and Hippocampus guttulatus. From 2011 to 2014, data were collected from 20 sites along the Apulian coast (Southern Italy) in order to cover a wide range of coastal marine, open water, and lagoon sites, from the surface to a depth of 48 metres. Seahorses were found at seven of the 20 sites investigated. Both species displayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 53 publications
5
29
0
Order By: Relevance
“…As for habitats, analyses did not reveal the existence of any relationship between habitat types and movement degree neither in terms of home range sizes nor in maximum distances. The availability of multiple habitats can induce specimens to choose and remain in a restricted area by moving from one habitat to another, which is an observation that seems consistent with the patchy distribution of seahorses (Curtis and Vincent 2005;Lazic et al 2018). However, the results of the present study indicated the seahorse preferences towards complex habitats (such as VS, rich in both animal and vegetal communities, and SBR in which many algal species grow), following previous studies (Gristina et al 2017;Lazic et al 2018), and the higher density of individuals in these habitats did not induce greater movements.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…As for habitats, analyses did not reveal the existence of any relationship between habitat types and movement degree neither in terms of home range sizes nor in maximum distances. The availability of multiple habitats can induce specimens to choose and remain in a restricted area by moving from one habitat to another, which is an observation that seems consistent with the patchy distribution of seahorses (Curtis and Vincent 2005;Lazic et al 2018). However, the results of the present study indicated the seahorse preferences towards complex habitats (such as VS, rich in both animal and vegetal communities, and SBR in which many algal species grow), following previous studies (Gristina et al 2017;Lazic et al 2018), and the higher density of individuals in these habitats did not induce greater movements.…”
Section: Discussionmentioning
confidence: 65%
“…As for the Mediterranean Sea, although some data on space use of H. guttulatus are available (Curtis and Vincent 2006;Garrick-Maidment et al 2010;Caldwell and Vincent, 2012), further information on its ecological attributes, including spatial distribution and site fidelity, movement patterns and home range size, might be crucial for successful conservation of the species. Through mark-recapture experiment at Mar Piccolo of Taranto, a site that hosts one of the most important Mediterranean populations of seahorses (Gristina et al 2015;Lazic et al 2018;Ape et al 2019), the present study allowed the arguing of the importance of considering a combination of time scales and different processes when studying H. guttulatus movement patterns. Data indicated an overall high site fidelity and modest species movements, but also highlighted the existence of variability among individuals, probably due to both abiotic (habitat availability) and biotic (life cycle stage, sex) factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations